2017
DOI: 10.1016/j.jjcc.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of venous thromboembolism recurrence and the bleeding events identified using a Japanese healthcare database

Abstract: These findings obtained from healthcare database suggest predictors either for recurrent VTE and bleeding that should be considered when selecting treatment to reduce the risk of recurrent VTE and mitigate bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In this study, 1.8- and 1.6-fold increased risks of VTE were found for male and female antipsychotic users, respectively. In a cohort study [ 50 ] undertaken in a Japanese acute-care hospital, the rate of recurrence of VTE events was 7.2 per 100 patient-years in patients with a previous VTE. Three predictors for recurrent VTE were identified: malignant disease, antipsychotic drug use and non-steroidal anti-inflammatory drug (NSAID) use.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…In this study, 1.8- and 1.6-fold increased risks of VTE were found for male and female antipsychotic users, respectively. In a cohort study [ 50 ] undertaken in a Japanese acute-care hospital, the rate of recurrence of VTE events was 7.2 per 100 patient-years in patients with a previous VTE. Three predictors for recurrent VTE were identified: malignant disease, antipsychotic drug use and non-steroidal anti-inflammatory drug (NSAID) use.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…50% of patients with image-proved DVT are asymptomatic. 1 Thrombus that does not lead to complete venous obstruction is silent. Many clinical and surgical circumstances not only lead to the development of DVT but also can occur in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of recurrent VTE while on anticoagulant treatment is particularly high in patients with cancer, as is the risk of bleeding complications [8][9][10][11]. Using a Japanese healthcare database, Nakamura et al also demonstrated that malignant disease was a predictor of recurrent VTE as well as bleeding [12].…”
Section: Introductionmentioning
confidence: 99%